Influence of Synchronization Protocols on Estrus Expression and its Intensity in Surti Goats - Sharma, Hitendra C; Khasatiya, Chandubhai T; Singh, Virendra K; Modi, Lalit C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present work was conducted to study the influence of different synchronization protocols on estrus expression and its intensity in Surti goats. Thirty goats were selected and divided into five equal groups (n=6 each). The goats of groups G1, G2 and G3 were implanted with intra-vaginal progestagen sponges (IVPS) for 11 days, without and with exposure to buck in G1 and G2, and with injection of 125 μg cloprostenol at the time of sponge removal in G3 group. Animals of group G4 were exposed to buck only for 11 days, while group G5 acted as control without any treatment or buck exposure. Estrus detection was performed by apronized bucks. Estrus intensity was determined based on behavioural and physiological signs associated with estrus. The mean scores, scales and ranks for estrus intensity did not differ significantly (p>0.05) between the groups. However, group G3 had highest mean score, scale and rank for estrus intensity, while overall the maximum frequency of behavioral signs was wagging of tail (100.00%), standing to be mounted (96.67%) and clustering around buck (93.33%). It was thus concluded that expression of induced estrus was similar to natural estrus and none of the synchronization protocols significantly influenced the pattern of estrus expression and its intensity in Surti goats.
Keywords: Estrus expression; Estrus intensity; Intra-vaginal progestagen sponges; Surti goats; Synchronization protocols